2022
DOI: 10.3390/membranes12040418
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Thermophilic and Mesophilic Membrane-Aerated Biofilm Reactors—A Modeling Study

Abstract: The concept of thermophilic membrane-aerated biofilm reactor (ThMABR) is studied by modeling. This concept combines the advantages and overcomes the disadvantages of conventional MABR and thermophilic aerobic biological treatment and has great potential to develop a new type of ultra-compact, highly efficient bioreactor for high-strength wastewater and waste gas treatments. Mathematical modeling was conducted to investigate the impact of temperature (mesophilic vs. thermophilic) and oxygen partial pressure on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Cunha et al [ 14 ] characterized water dynamics in cellulose acetate-silica asymmetric membranes by combining multiple methods, including 1 H NMR spectroscopy, diffusometry and relaxometry. In the research conducted by Lu, Bai, and Liao [ 15 ], mathematical modeling was utilized to examine the impact of temperature (mesophilic versus thermophilic) and oxygen partial pressure on the performance of the membrane-aerated biofilm reactor (MABR), and the results indicated that ThMABR had significant advantages over conventional mesophilic MABR. Zou et al [ 16 ] investigated the role of Ca 2+ addition in humic acid (HA) fouling and the potential of adding Ca 2+ for fouling mitigation in the coagulation-ultrafiltration process.…”
mentioning
confidence: 99%
“…Cunha et al [ 14 ] characterized water dynamics in cellulose acetate-silica asymmetric membranes by combining multiple methods, including 1 H NMR spectroscopy, diffusometry and relaxometry. In the research conducted by Lu, Bai, and Liao [ 15 ], mathematical modeling was utilized to examine the impact of temperature (mesophilic versus thermophilic) and oxygen partial pressure on the performance of the membrane-aerated biofilm reactor (MABR), and the results indicated that ThMABR had significant advantages over conventional mesophilic MABR. Zou et al [ 16 ] investigated the role of Ca 2+ addition in humic acid (HA) fouling and the potential of adding Ca 2+ for fouling mitigation in the coagulation-ultrafiltration process.…”
mentioning
confidence: 99%